แนวทางการพัฒนาภาวะผู้นำเชิงพหุวัฒนธรรมของผู้บริหาร วิทยาลัยนานาชาติเพื่อศึกษาความยั่งยืน มหาวิทยาลัยศรีนครินทรวิโรฒ - อารมณ์ชื่น, จีรุทม์ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 3 (2567): กันยายน-ธันวาคม 2567, 2024)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาปัญหาและแนวทางการพัฒนาภาวะผู้นำเชิงพหุวัฒนธรรมของผู้บริหารวิทยาลัยนานาชาติเพื่อศึกษาความยั่งยืน มหาวิทยาลัยศรีนครินทรวิโรฒ กลุ่มเป้าหมายในการสัมภาษณ์ ได้แก่ ผู้บริหารระดับสูงและระดับกลาง วิทยาลัยนานาชาติเพื่อศึกษาความยั่งยืน จำนวน 5 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูลเป็นแบบสัมภาษณ์แบบมีโครงสร้าง โดยใช้การสัมภาษณ์แบบเจาะลึก วิเคราะห์ข้อมูลโดยใช้การวิเคราะห์เนื้อหา ผลการวิจัยพบว่า ปัญหาของการบริหารองค์กรพหุวัฒนธรรม คือ กระบวนการและทัศนคติในการทำงานของผู้ที่มีความแตกต่างหลากหลายทั้งด้านอายุ ภาษา เชื้อชาติ และวัฒนธรรม แนวทางการพัฒนาภาวะผู้นำเชิงพหุวัฒนธรรมของผู้บริหาร คือ การใช้กระบวนการสื่อสารที่มีคุณภาพ และส่งเสริมการยอมรับความแตกต่างหลากหลายทางวัฒนธรรมของคนในองค์กร โดยผู้นำควรปฏิบัติตนเป็นตัวอย่างในการอยู่ร่วมกันท่ามกลางพหุวัฒนธรรมอย่างเหมาะสม จัดการส่งเสริมวัฒนธรรมอย่างหลากหลายบนพื้นฐานของการให้คุณค่าทุกคนอย่างเท่าเทียม The objective of this research is to examine the challenges and guidelines for promoting multicultural leadership among executives at the International Colleges for Sustainability Studies, Srinakharinwirot University. The target group for the interviews consisted of senior and mid-level executives from the International College for Sustainability Studies, totaling five individuals. Data was collected through structured interviews, and an in-depth analysis approach utilizing content analysis was employed for data interpretation. The study revealed that the effective management of a multicultural organization depends on the attitudes and behaviors of individuals varying in age, language, race, and culture within the workplace. To establish guidelines for multicultural leadership among executives, it is essential to implement a communication process that prioritizes high-quality interactions and promotes acceptance of cultural diversity among organizational members. In this effort, leaders should assume a pivotal role, acting as role models to showcase harmonious coexistence amidst cultural diversity. They can achieve this by organizing and promoting diverse cultures within the organization, valuing everyone equally, and thereby creating an inclusive and supportive environment.